Exploration of PAI Teacher Challenges and Opportunities; Case Study of Implementation The Independent Learning Curriculum, In East Lombok Elementary Schools - Rasyidi, Abdul Haris; Idrus, S. Abdul Jalil Al (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Education in Indonesia is experiencing a significant transformation, one of the concrete steps in dealing with this development is the implementation of the Independent Learning Curriculum. The Independent Learning Curriculum carries the principle of inclusivity and views every child as an individual who has unique potential, however it still has several challenges and opportunities for Islamic religious education teachers. This study focuses on the challenges of Islamic religious education teachers in implementing, knowing opportunities for teachers and analysing the role of the independent learning curriculum in learning Islamic religious education in elementary schools. The method in this research is a case study using a qualitative design with a phenomenological approach. Data collection techniques use semi-structured interviews, observation and documentation techniques. Data sources are PAI teachers, school principals and PAI Teacher Working Groups in 32 elementary schools in East Lombok. Thematic analysis is used to analysis the extent to which curriculum implementation can be implemented. The results of the research identified several challenges faced by PAI teachers, including adapting student-focused learning approaches, limited resources and infrastructure and strengthening curriculum evaluation. Other findings include opportunities for PAI teachers to utilize technology, increase student engagement, collaboration between subjects for cross-disciplinary learning and an emphasis on developing student skills. In conclusion, PAI teachers need to strive to align PAI learning with curriculum vision and principles that include student-based, contextual and collaborative learning. Meanwhile, opportunities that can be exploited include making PAI learning more interesting, relevant and collaborative and PAI teachers being able to utilize the role of the independent learning curriculum as an opportunity to improve the quality of Islamic religious education in elementary schools, helping students understand religious values and teachings, and being able to support character education efforts based on moral values.